Human Resource Accounting: Recognition and Disclosure of Accounting Methods (Global Journal of Management and Business Research, 2013)
HRA is the process of identifying, measuring data about human resources and communicating this information to interested parties the major objects of the study is to highlight the major characteristics of HRA along with the practical benefits and difficulties in implementations. The study forms mainly the extensive review of related literature based on highly work. The major benefits of such accounting are that it develops effective managerial decision making, quality of management, prevents misuse of human resources, increases human asset productivity, improves morale, job satisfaction and creativity, etc. The constraints involved are that uncertainty of human resources creates uncertainty in valuation of human resources. Nature of amortization is another difficulty, valuation of human resources, their accounting treatments is also difficult as there is no specific IAS/IFRS for such treatment.
Keywords: human resources; management; accounting treatments; human resources capital